Identification and measurement of intangibles in a knowledge economy: The special relevance of human capital - Nadine Allar (European Institute for Knowledge & Value Management (EIKV), 2017)
Motivation for the topic: Prior to the work on this paper I was involved in several constructive discussions on intangibles and their importance for companies with participants of various professional backgrounds. The first reaction when I explained my aim to provide a base for the measurement of factors like knowledge and motivation has often been: `That is impossible.' In the further course of discussions diverse questions arose, as for example `Why should we try do measure these values?', `How could companies show these values in their balance sheets?', as well as `Is it ethical to treat human beings simply like assets?' to name only a few of them. - Research question: Especially in knowledge economies, intangibles constitute a major factor of value for individuals and organizations. However, it is not easy to detect the economic value of several intangible elements. While the importance of one part of intangibles has been realized, another part is often left aside. Reasons might be a lack of focus on these intangibles and difficulties when it comes to valuation and measurement. Analysing the balance sheets of companies, intellectual properties like for example patents are reported. So the question is whether to report intellectual capital as well. Before organizations take on this objection, there are several further obstacles, they face. The identification of intangibles as assets, the determination of a valuation method as well as the awareness of its potential and benefits remain challenges. Discussions about the topic should contain several perspectives: the economic perspective, the relation to international accounting and corresponding regulations as well as the question on taxation. The present paper will focus mainly on the economic perspective. Several aspects have been identified to focus on: * Importance of intangibles for companies * Most important assets, employees provide to their companies * Awareness of companies and recruiters about these assets * Demand for intangibles * Methods for valuation of intangibles.
Keywords: 330